2015
DOI: 10.1063/1.4914167
|View full text |Cite
|
Sign up to set email alerts
|

Dust-lower-hybrid instability with fluctuating charge in quantum plasmas

Abstract: The instability of Dust-Lower-Hybrid (DLH) wave is examined in detail in the uniform dusty magnetoplasmas. The time dependent charging effects on dust particles around its equilibrium charge Qd0 are taken into account based on Orbit-Limited Probe theory. The quantum characteristics of the system like Bohm potential and Fermi degenerate pressure are dealt using the quantum hydrodynamic model of plasmas. The external magnetic field and size of the dust particles have new physical effects over the dissipative ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Very recently, the wave probation and instability have been extensively explored in quantum dusty plasmas (Jamil et al. 2014, 2015) including the quantum-mechanical effects. Hence, the quantum-mechanical and nonlinear ion wake-field effects on the dust-lattice wave in complex quantum dusty plasmas will be treated elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the wave probation and instability have been extensively explored in quantum dusty plasmas (Jamil et al. 2014, 2015) including the quantum-mechanical effects. Hence, the quantum-mechanical and nonlinear ion wake-field effects on the dust-lattice wave in complex quantum dusty plasmas will be treated elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is expected that the simple analytic expressions of Equations (10), (12) and (13) provide the statistical averaged information contents for atomic states in strongly coupled plasma. Very recently, the thermodynamic properties of degenerate electron systems have been extensively explored, including the quantum phenomena such as the electron exchange-correlation, quantum diffraction, and quantum recoil effects [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Hence, the Shannon information entropy for atomic data investigated in degenerate quantum plasma will also be explored elsewhere.…”
Section: Theory and Calculationsmentioning
confidence: 99%
“…For example, Ref. [39] used the following "typical parameters...for the interiors of the neutron stars, the magnetars, and the white dwarfs...": a dust density of 10 18 cm −3 and a dust radius a d ∼ 10 −5 cm. One readily verifies that, at this density, the mean nearest neighbor distance of two dust particles is less than 10 −6 cm, i.e., more than an order of magnitude smaller than the dust radius.…”
Section: Test Of Quantum Dusty Plasma Parameters Used In the Literaturementioning
confidence: 99%
“…The work [8] has been followed by a large number of papers on QDP that were dedicated to important plasma physics phenomena, such as the Jeans instability [9][10][11][12][13][14], different types of dust ion acoustic waves , the dust-lower-hybrid instability [38,39], new low-frequency oscillations [40], plasma waves and instabilities under a gravitational field [41,42], screening effects [43], and nonlinear ion acoustic waves [44]. These and related studies demonstrated that the inclusion of charged dust particles leads to a broad set of waves and oscillations that is much richer than in "ordinary" electron-ion quantum plasmas (see e.g.…”
Section: Introductionmentioning
confidence: 99%